SALAMA: Swahili Language Manager (Nordic Journal of African Studies, 1999)
SALAMA is an acronym for Swahili Language Manager. It is a computerised working environment, where it is possible, with the help of a set of programs and user-defined utilities, to perform a multitude of tasks. For introducing SALAMA, it is perhaps more interesting to describe its aims and applications first, and then give an outlay of its components. Appendix 1 gives an overall view of the structure of the system, and of some of its applications. In this paper it is possible to give only a brief and condensed description of how the system is constructed. It is without any technical detail as to how the system is implemented. For those interested in more detailed description of the components, a list of relevant publications is added in the end of the paper. References to those are also made in text.